2010
DOI: 10.1002/pssa.200982803
|View full text |Cite
|
Sign up to set email alerts
|

Passivation study of the amorphous–crystalline silicon interface formed using DC saddle‐field glow discharge

Abstract: Phone: þ00 1 416 946 7372, Fax: þ00 1 416 971 2326The DC saddle-field (DCSF) glow discharge method was used to deposit intrinsic a-Si:H onto c-Si to passivate the c-Si surface. The effective minority carrier lifetime in the heterostructures as a function of the excess minority carrier density in the c-Si wafers was measured. The results were then analyzed in the context of recombination associated with interface defect states using three known recombination models. The defect density and the charge density at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…2, N s changes significantly with samples prepared using different conditions, however, the fitted Q s for all samples remained constant at approximately 1.0×10 11 cm −2 . This is consistent with results reported in other studies [6,14] which show that N s is the primary parameter which determines the passivation quality for samples passivated with intrinsic a-Si:H (e.g., i-a-Si:H/n-c-Si/ i-a-Si:H). As a result, only the N s values for different samples are quoted in the remaining sections of this paper.…”
Section: Modelling Of the A-si:h-c-si Heterointerfacesupporting
confidence: 92%
See 2 more Smart Citations
“…2, N s changes significantly with samples prepared using different conditions, however, the fitted Q s for all samples remained constant at approximately 1.0×10 11 cm −2 . This is consistent with results reported in other studies [6,14] which show that N s is the primary parameter which determines the passivation quality for samples passivated with intrinsic a-Si:H (e.g., i-a-Si:H/n-c-Si/ i-a-Si:H). As a result, only the N s values for different samples are quoted in the remaining sections of this paper.…”
Section: Modelling Of the A-si:h-c-si Heterointerfacesupporting
confidence: 92%
“…In this paper, the interface defect density is inferred by applying a simple closed form (SCF) model described in detail in [14,32]. This model has two variable parameters -the interface defect density (N s ) and the interface charge density (Q s ).…”
Section: Modelling Of the A-si:h-c-si Heterointerfacementioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the cathodes and the substrate were all held at ground potential. Using this DC saddle field configuration in a previous study we have reported passivation results showing effective lifetimes exceeding 1 ms [3].…”
Section: Saddle Field Plasma Enhanced Chemical Vapor Depositionmentioning
confidence: 90%
“…This saddle-field configuration promotes the oscillation of electrons about the anode, resulting in a much longer electron mean free path, which in turn increases the probability of interaction with gas-phase species and thus allows for a stable plasma at much lower pressures than is normally possible with a DC diode. The semi-transparent cathode, which permits plasma species to diffuse to the substrate, serves to isolate the substrate from the plasma region proper thereby allowing the plasma parameters and the substrate parameters to be controlled independently [3,4]. In addition to the remote plasma, the energy of the ionic species arriving at the substrate can be modulated by varying the substrate and semitransparent cathode potentials.…”
Section: Saddle Field Plasma Enhanced Chemical Vapor Depositionmentioning
confidence: 99%